2004
DOI: 10.1089/105072504322880364
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Ethanol Injection Treatment in Benign Thyroid Lesions: Role and Efficacy

Abstract: Most recurrent cystic lesions of the thyroid can be cured by PEI, which should become the first line of treatment. The majority of AFTN and toxic nodules with volume less than 5.0 mL presented a marked volume decrease and normal serum TSH levels when treated by PEI, which seems a valid alternative to clinical follow-up alone in patients refusing 131I. PEI is not indicated in large or toxic nodules, for which 131I is the treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
86
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 39 publications
1
86
0
9
Order By: Relevance
“…Thyroid function is normalized after ethanol injection in approximately 60%-80% of pretoxic nodules and 35%-85% of toxic nodules. 3 Tarantino et al 4 reported complete cure (absent uptake in the nodule and recovery of normal uptake in the thyroid parenchyma) in 93% of patients with AFTNs. After laser ablation, cure rates of 61%-100% have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thyroid function is normalized after ethanol injection in approximately 60%-80% of pretoxic nodules and 35%-85% of toxic nodules. 3 Tarantino et al 4 reported complete cure (absent uptake in the nodule and recovery of normal uptake in the thyroid parenchyma) in 93% of patients with AFTNs. After laser ablation, cure rates of 61%-100% have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was not indicated because of the small size of the nodule and the patient's reservation toward surgery. Alternative treatments, such as ethanol injection, 3,4 laser, 6,12,13 or radio-frequency ablation, 5 have been reported. Thyroid function is normalized after ethanol injection in approximately 60%-80% of pretoxic nodules and 35%-85% of toxic nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When nodules are cystic or predominantly cystic, percutaneous ethanol injection (PEI) represents a valuable minimally invasive treatment strategy [15][16][17][18][19], with a reported success rate of 82-85 % (volume reduction [85 % from baseline) after an average of two sessions [19][20][21][22]. However, there are several limitations to the use of this technique for solid nodules; these are related to the difficulty in predicting the diffusion of the ethanol within the nodule, the leakage-induced pain, and the possibility of extra-glandular fibrosis making subsequent surgery more complex [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…US-guided percutaneous ethanol injection (PEI) therapy is currently considered one of the first-line treatment modality for cystic and predominantly cystic nodules (2,3). Laser ablation (LA) has been proposed as a safe outpatient procedure that effectively reduces the volume of solid nodules and the clinical outcomes in the majority of patients (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%